Stress Tolerance and Organic Acid Productivity of Fungal Strains Isolated from Local Agricultural Sources - Osazuwa, Christopher (Jurnal Pangan dan Agroindustri, 2025)
Fungal diversity enhances industrial bioprocess efficiency and innovation. This study was aimed at isolating stress-tolerant fungal strains from local agricultural sources and evaluating their organic acid productivity. Fungal isolation and identification were performed using culture and molecular techniques. Agricultural sources such as cassava peels, palm wine, lignocellulosic waste, and fruit waste were utilized. Environmental stress tolerance and organic acid productivity were assessed using cultural methods. Aspergillus niger and Trichoderma viride showed highest tolerance to temperature and pH. Candida zeylanoides (2.80), Yarrowia lipolytica (2.94), Rhizopus arrhizus (2.58), and A. niger (3.12) were the most promising organic acid producers. Optimal conditions for organic acid production were found to be: 5-10% inoculum size, 30–35°C, pH 5.5–6.0, 144 hours fermentation time, 0.1–0.2%(w/v) nitrogen concentration. These findings indicate that stress tolerance significantly influences the organic acid productivity of these organisms, reinforcing the potential of these local isolates for sustainable bioprocess development.